2013
DOI: 10.1136/vropen-2014-000042
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire‐based survey on the uptake and use of cattle vaccines in the UK

Abstract: BackgroundVaccination is a widely used strategy for disease control in cattle in the UK and abroad. However, there has been limited research describing the uptake and use of cattle vaccines on UK farms.AimTo describe the current uptake and usage of cattle vaccines in the UK.DesignA questionnaire, available in paper and online format, was distributed to cattle farmers by convenience sampling.ParticipantsAll UK cattle farmers were eligible to participate in the study.ResultsEighty-six per cent of respondents (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(74 citation statements)
references
References 15 publications
4
67
1
2
Order By: Relevance
“…However, vaccines must be used appropriately to be effective. Vaccination regimes themselves can be complex and errors do occur, for example in maintaining the cold chain and in using multiple products at the same time (Cresswell et al, 2014). Farmer expectations about the effectiveness of vaccines needs to be carefully managed to avoid reliance on vaccination alone; whilst modern vaccines can be very effective, full protection is difficult to guarantee in the absence of any other control measures, due to poor compliance, insufficient immune response or an overwhelming challenge.…”
Section: Controlling the Risk From Existing Diseasementioning
confidence: 99%
“…However, vaccines must be used appropriately to be effective. Vaccination regimes themselves can be complex and errors do occur, for example in maintaining the cold chain and in using multiple products at the same time (Cresswell et al, 2014). Farmer expectations about the effectiveness of vaccines needs to be carefully managed to avoid reliance on vaccination alone; whilst modern vaccines can be very effective, full protection is difficult to guarantee in the absence of any other control measures, due to poor compliance, insufficient immune response or an overwhelming challenge.…”
Section: Controlling the Risk From Existing Diseasementioning
confidence: 99%
“…With vets administering vaccines on farm in only 6 percent of cases in the UK (Cresswell and others 2014), responsibility for the administration of vaccines and other veterinary medicines largely falls on farmers and farm workers. It is unknown how aware farmers are of the need to keep vaccines within specified temperature ranges until they are administered to an animal.…”
Section: Usage and Handlingmentioning
confidence: 99%
“…For example, some vaccines are required to be brought up to ambient temperatures of 15 to 25°C before administration. Although this information is on the datasheet, Cresswell and others (2014) found that only about one third of farmers refer to the datasheet before starting a vaccination session. Unfortunately, there are limited published data on the actual effect on efficacy of the vaccine when it is not administered at the correct temperature, so more research in this area could help farmers and vets focus on the key areas to improve.…”
Section: Usage and Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Vaccinations are commonly used to protect calves against diarrhoea and respiratory disease on UK dairy farms, as highlighted by a recent study reporting that 75 per cent of dairy farmers were vaccinating calves up to the age of six months (Cresswell and others 2014). The same study reported higher use of respiratory and clostridial vaccines in beef calves, compared with dairy calves, except for lungworm, for which less than 5 per cent of beef animals were vaccinated, compared to a third of dairy animals.…”
Section: Vaccination: When and Where To Start?mentioning
confidence: 99%